ANALISIS HARGA SAHAM PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER DI BURSA EFEK INDONESIA - Maharani Pratiwi (2022)
In this quantitative study, the purpose of this research is to analyze the effect of Liquidity, Activity, Profitability and Exchange Rate on Stock Prices of Companies in the Primary Consumer Goods Sector on the Indonesia Stock Exchange. The population in this study examines primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The method of determining the sample used is probability sampling with the slovin technique, obtained 53 companies and the research period is 5 years, so that 265 research data are obtained. The data analysis technique uses Panel Data Regression Analysis with Eviews 12 and a significance level of 5%. In the study, explaining the results, namely Liquidity with the Current Ratio (CR) proxy has no effect on stock prices, Activity with the Total Asset Turnover (TATO) proxy has no effect on stock prices, Profitability with Return on Equity (ROE) proxies has a positive effect on stock prices, value exchange with proxies The middle rate has a negative effect on stock prices. Key words : stock price, liquidity, activity, profitability and exchange rate